Impact of media attention on corporate green innovation: what is the role of dual environmental regulation? - Chen, Ning; Yan, Nan; Xie, Henglang; Ou, Yifan (Elsevier, 2024)
This study explores the intricate interplay between media attention, dual environmental regulation, and corporate green innovation quality using a comprehensive dataset of Chinese A-share listed companies. Thus, our rigorous empirical analysis reveals that media visibility significantly affects corporate environmental sustainability efforts, with formal and informal environmental regulations moderating its impact. Media attention acts as a powerful catalyst for green innovation during growth and mature stages of a company's lifecycle; however, its effect diminishes during recessions. We determine significant heterogeneity across industry types and ownership structures. Non-high-polluting industries and non-state-owned enterprises show stronger positive responses to media scrutiny in their green innovation efforts than high-polluting sectors and state-owned enterprises. Furthermore, formal environmental regulations amplify the positive effect of media attention on green innovation, suggesting a synergistic potential that encourages companies to exceed baseline environmental standards. In contrast, while having no direct impact on green innovation, informal environmental regulation significantly moderates the relationship between media attention and innovation quality. These findings add to the literature on environmental innovation by demonstrating the conditional effectiveness of media attention and the critical role of regulatory frameworks in fostering sustainable corporate practices across industries and ownership contexts, with implications for policymakers, corporate strategists, and environmental advocates.